Heatstroke due to Vehicular Entrapment: An Autopsy Case Report - Razuin R1,2., Julina M. N3 , Nurquin F. S.2 , Amirul A. H.2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Heatstroke is defined as severe heat illness with elevated body temperature greater than 40.6?C associated with central nervous system dysfunction. In children, heatstroke as a result of vehicular entrapment is commonly encountered. We report a case of a six-year-old boy who was accidentally left in a school van under scorching hot afternoon for several hours. Upon discovery, he was rushed to a hospital where he was pronounced dead. His body temperature taken at the Emergency Department was 40.3?C. The body felt warm in spite of apparent presence of post mortem changes such as rigor and livor mortis. His clothes were drenched in sweat. A medico-legal autopsy was performed. On general examination, his body was pale and the lips were also parched and pale. Internally, there was subdural haemorrhage and petechial haemorrhages on the lungs and the epicardial surface of the heart. The cause of death was given as heatstroke as a result of vehicular entrapment. We wish to emphasize and appeal to the public that this tragic incident is preventable. Public and private sectors should help creating awareness of dangers in leaving a child unattended in a car